Different Effects of 2 mA and 4 mA Transcranial Direct Current Stimulation on Muscle Activity and Torque in a Maximal Isokinetic Fatigue Task - Workman, Craig David; Fietsam, Alexandra C.; Rudroff, Thorsten (Frontiers in Human Neuroscience, 2020)
Motor Studies investigating the effects of transcranial direct current stimulation (tDCS) on fatigue and muscle activity have elicited measurable improvements using stimulation intensities ≤ 2 mA and submaximal effort tasks. The purpose of this study was to determine the effects of 2 mA and 4 mA anodal tDCS over the primary motor cortex (M1) on performance fatigability and electromyographic (EMG) activity of the leg muscles in healthy young adults. A double-blind, randomized, sham-controlled cross-over study design was applied. Twenty-seven active young adults completed four sessions, each spaced by 5 – 8 days. During Session 1, dominance was verified with isokinetic strength testing and subjects were familiarized with the fatigue task (FT). The FT protocol included 40 continuous maximum isokinetic contractions of the knee extensors and flexors (120°/s, concentric/concentric). During Sessions 2 – 4, tDCS was applied for 20 min with one of three randomly assigned intensities (sham, 2 mA or 4 mA) and the FT was repeated. The anode and cathode of the tDCS device were placed over C3 and the contralateral supraorbital area, respectively. A wireless EMG system collected muscle activity during the FT. The 2 mA tDCS condition had significantly less torque (65.9 ± 32.7 Nm) during the FT than both the sham (68.4 ± 33.9 Nm, p < 0.001) and 4 mA conditions (68.4 ± 33.9 Nm, p = 0.001).Furthermore, the 2 mA condition (33.8 ± 11.7%) had significantly less EMG activity during the FT than both the sham (39.7 ± 10.6%, p < 0.001) and 4 mA conditions (40.5 ± 13.4%, p = 0.001). Contrary to previous submaximal isometric fatigue investigations, the 2 mA tDCS condition significantly reduced torque production and EMG activity of the leg extensors during a maximal isokinetic fatigue task compared with the sham and 4 mA conditions. In addition, torque production and EMG activity in the 4 mA condition were not significantly different from sham. Thus, the effects of tDCS, and the underlying mechanisms, might be different for maximal and submaximal tasks and warrants more investigation.